Immunophenotyping characteristics of COVID‐19 patients: Peripheral blood CD8+ HLA‐DR+ T cells as a biomarker for mortality outcome - Mirsharif, Ensie Sadat; Chenary, Maryam Rajabnia; Bozorgmehr, Mahmood; Mohammadi, Saeed; Hashemi, Seyed Mahmoud; Ardestani, Susan Kabudanian; Beigmohammadi, Mohammad‐Taghi; Abdollahi, Alireza; Sadeghipour, Alireza; Kariminia, Amina; Tuserkani, Fatemeh; Ghazanfari, Tooba (Journal of medical virology, 2023)
Introduction The goal of this study was to identify biomarker(s) to assign risk of mortality in COVID‐19 patients to improve intensive care unit (ICU) and coronary care unit  management. A total of 100 confirmed COVID‐19 patients admitted at Imam Khomeini Hospital in Tehran, were compared to 70 control subjects. Peripheral blood leukocyte was studied using staining reagents included CD3, CD4, CD8, HLA‐DR, CD19, CD16, and CD56. The immunophenotyping analysis was evaluated using the FACSCalibur instrument. To investigate the cell density of lung infiltrating T cells, postmortem slides of needle necropsies taken from the lung tissue of 3 critical patients were evaluated by immunohistochemistry staining. The number of lymphocyte subpopulations was significantly lower in COVID‐19 patients than in the control group. Regarding the disease severity, the absolute count of T, NK, and HLA‐DR+ T cells were significantly reduced in severe patients compared to the moderate ones. The critical patients had a significantly lower count of CD8‐HLA‐DR+ T cells than the moderate cases. Regarding the disease mortality, based on univariate analysis, the count of HLA‐DR+ T, CD8− HLA‐DR+ T, and CD8+ HLA‐DR+ T cells was associated with mortality in COVID‐19 patients. Receiver operating characteristic curve analysis showed the count of CD8+ HLA‐DR+ T cells is the best candidate as a biomarker for mortality outcome. Furthermore, pulmonary infiltration of T cells in the lung tissue showed only slight infiltrations of CD3+ T cells, with an equal percentage of CD4+ and CD8+ T cell subpopulation in the lung tissue. These findings suggest that close monitoring of the value of CD8+ HLA‐DR+ T cells in COVID‐19 patients may be helpful to identify high‐risk patients. However, further studies with larger sample size are needed.